The child penalty: Implications of parenthood on labour market outcomes for men and women in Germany - Charlotte H. Feldhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Whilst gender inequality has been falling in the developed world, child-related gender inequality in pay has stayed constant. In this paper I use German panel data spanning across 33 years from 1984 until 2017 including over 50,000 individuals. The main contribution of this paper is the analysis of the effect of parenthood on women's and men's earnings using propensity score matching. I estimate the annual average treatment effect of parenthood over the 20 years following the birth of the first child to be -10500 exteuro for women and +6800 exteuro for men. When comparing the percentage loss of potential earnings, I find that women suffer a long-run child penalty of 63% compared to men. I then examine the relationship between the treatment effect and gender norms, willingness to take on risk for your career and priorities regarding job characteristics. There exists evidence which suggests that all of these factors are associated with changes in the individual treatment effects.
Keywords: J13; J16; J21; J31; C12; C13; 330; Gender Economics; Child Penalty; Propensity Score Matching